Measurement of Omega(m), Omega(Lambda) from a blind analysis of type Ia supernovae with CMAGIC: Using color information to verify the acceleration of the universe - Conley, A; Goldhaber, G; Wang, L; Aldering, G; Amanullah, R; Commins, E; Fadeyev, V; Folatelli, G; Garavini, G; Gibbons, R; Goobar, A; Groom, D; et al. (Institute of Physics Publishing, 2006)
We present measurements of Ωm and Ω Λ from a blind analysis of 21 high-redshift supemovae using a new technique (CMAGIC) for fitting the multicolor light curves of Type la supernovae, first introduced by Wang and coworkers. CMAGIC takes advantage of the remarkably simple behavior of Type la supernovae on color-magnitude diagrams and has several advantages over current techniques based on maximum magnitudes. Among these are a reduced sensitivity to host galaxy dust extinction, a shallower luminosity-width relation, and the relative simplicity of the fitting procedure. This allows us to provide a cross-check of previous supernova cosmology results, despite the fact that current data sets were not observed in a manner optimized for CMAGIC. We describe the details of our novel blindness procedure, which is designed to prevent experimenter bias. The data are broadly consistent with the picture of an accelerating universe and agree with a flat universe within 1.7 σ, including systematics. We also compare the CMAGIC results directly with those of a maximum magnitude fit to the same supernovae, finding that CMAGIC favors more acceleration at the 1.6 σ level, including systematics and the correlation between the two measurements. A fit for w assuming a flat universe yields a value that is consistent with a cosmological constant within 1.2 σ. © 2006. The American Astronomical Society. All rights reserved.